Study on the effects of stand density management of Chinese fir plantation in Northern China - Sun, Kun; Sun, Honggang; Lu, Guobin; Fang, Lejen; Wan, Zhibing; Tan, Zifeng (Frontiers in Plant Science, 2023)
The aim of this study was to clarify the mechanism by which thinning alters stand structure and affects forest productivity by characterizing changes in stand quantitative maturity age, stand diameter distribution, structural heterogeneity, and forest productivity of Chinese fir plantations at different thinning times and intensities. Our findings provide insights into how the density of stands could be modified to enhance the yield and timber quality of Chinese fir plantations. The stand quantitative maturity age was obtained using the Richards equation. The quantitative relationship between stand structure and productivity was determined using a generalized linear mixed model. We found that (1) the quantitative maturity age of Chinese fir plantations increased with thinning intensity, and the quantitative maturity age was much greater under commercial thinning than under pre-commercial thinning. (2) Thinning promoted increases in stand diameter. Pre-commercially thinned stands were dominated by medium-diameter trees when the quantitative maturity age was reached, whereas commercially thinned stands were dominated by large-diameter trees. (3) Thinning also reduced heterogeneity in stand structure, which was lower after commercial thinning than after pre-commercial thinning. (4) Individual tree volume and the proportion of medium-sized and large-sized timber merchantable volume increased with stand thinning intensity. The productivity of pre-commercially thinned stands increased with thinning intensity, whereas that of commercially thinned stands decreased with thinning intensity. (5) The structural heterogeneity of pre-commercially and commercially thinned stands was negatively and positively correlated with forest productivity, respectively. In conclusion, when pre-commercial thinning was performed in the ninth year to a residual density of 2,500 trees per hectare, the stand quantitative maturity age was reached in year 26, medium-sized timber accounted for 64.3% of all trees, and the stand volume was 403.9 m3 per hectare. This thinning strategy is favorable for producing medium-sized Chinese fir timber. When commercial thinning was performed in year 23, the optimal residual density was 400 trees per hectare. When the stand quantitative maturity age was reached in year 31, large-sized timber accounted for 72.4% of all trees, and the stand volume was 121.2 m3 per hectare. This thinning strategy is favorable for producing large-sized Chinese fir timber.